Fibrodysplasia ossificans progressiva: case report Fibrodisplasia ossificante progressiva: relato de caso - Andre Leite Gonçalves; Marcelo Rodrigues Masruha; Carmelinda Correia de Campos; Patricia Longo Ribeiro Delai; Luiz Celso Pereira Vilanova (Arquivos de Neuro-Psiquiatria, 2005)
Fibrodysplasia ossificans progressiva (FOP) is a rare autosomal dominant disorder characterized by postnatal progressive heterotopic ossification of the connective tissue and congenital malformation of the big toes. We report on a nine-year-old girl with clinical and radiological features of FOP. She was born with bilateral hallux valgus and at the age of nine presented an indurate mass in the left cervical region that was painful. A significant decreased range of motion in all levels of the spine and shoulder girdle was found. The radiographs showed heterotopic ossification in the thoracic region. The patient had two outbreaks of the disease ("flare-ups") that were treated with prednisone 2 mg/kg/day for four days. After the "flare-ups", she had a continuous therapy with a Cox-2 inhibitor (25 mg/day) and a leukotriene inhibitor, montelukast (10 mg/day). A fibrodisplasia ossificante progressiva (FOP) é doença rara, autossômica dominante, caracterizada por ossificação heterotópica progressiva pós-natal do tecido conjuntivo e malformação congênita dos háluces. Relatamos o caso de menina de nove anos com o quadro clínico-radiológico típico de FOP, nascida com hálux valgo bilateral e que aos 9 anos de idade apresentou massa dolorosa, de consistência endurecida, sem sinais inflamatórios, situada na região cervical. Adicionalmente, era possível observar diminuição importante da movimentação em todos os níveis da coluna vertebral e da cintura escapular. A avaliação radiológica revelou a presença de ossificações heterotópicas na região torácica e malformação bilateral dos háluces. A paciente teve outros dois surtos da doença, que foram tratados com corticosteróide oral por quatro dias, (2 mg/kg/dia) seguido por tratamento prolongado com inibidores da Cox-2 (25 mg/dia) e com inibidor de leucotrienos (10 mg/dia).